Deregulating Job Placement in Europe: A Microeconometric Evaluation of an Innovative Voucher Scheme in Germany - Henrik Winterhager; Anja Heinze; Alexander Spermann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Job placement vouchers can be regarded as a tool to spur competition between public and private job placement activities. The German government launched this instrument in order to end the public placement monopoly and to subsidize its private competitors. We exploit very rich administrative data provided for the first time by the Federal Employment Agency and apply propensity score matching as a method to solve the fundamental evaluation problem and to estimate the effect of the vouchers. We find positive treatment effects on the employment probability after one year of 6.5 percentage points in Western Germany and give a measure for deadweight loss.
Keywords: H25; J68; 330; Job Placement; Active Labor Market Policy; Matching; Arbeitsvermittlung; Voucher; Personalberatung; Wirtschaftspolitische Wirkungsanalyse; Arbeitslosigkeit; Deutschland